Microstructures and Mechanical Properties of Different Mass Fractions of Ti-Coated Diamond/FeNiCrCuAl High Entropy Alloy Composites Prepared by Spark Plasma Sintering - Zhixin Wang; Jiangtao Li; Mengjie Pei; Mingxing Ma; Xiaozhe Cheng; Qian Zhang; Xiaoyan Guan; Huili Ding; Shaopei Jia; Qisong Li; Quan Huang (Archives of Metallurgy and Materials)
FeNiCrCuAl high-entropy alloy (HEA )/Ti-coated diamond composites were prepared by spark plasma sintering (SPS). The TiC coating was formed in situ on the surface of the diamonds through a vacuum micro-evaporation process. This study investigated the effects of varying mass fractions of diamonds (3 wt.%, 5 wt.%, 7 wt.%, and 12 wt.%) on the microstructure, microhardness, flexural strength, and wear properties of the high-entropy alloy. The results indicate that the TiC coating on the diamond surface effectively preserves the morphological integrity of the diamond within the FeNiCrCuAl HEA at an ambient temperature of 1000°C. Following sintering, the microstructure of the FeNiCrCuAl high-entropy alloy powder occurs transitions from a body-centered cubic (BCC) phase to a face-centered cubic (FCC) phase. As the mass fraction of diamonds increases, the hardness of the composites gradually increases. The composite containing 12 wt.% diamonds exhibits the highest hardness of 500.2 HV0.5 within the FeNiCrCuAl HEA matrix, which is approximately 15.7% greater than that of the composite without diamond addition. Conversely, the flexural strength decreases with the increase of the heterogeneous interfaces created by the diamonds in the composites. The flexural strength of the composite containing 12 wt.% diamonds is only 277.0 MPa, representing a 51.6% reduction compared to the FeNiCrCuAl HEA. The composite compared with 7 wt.% diamonds demonstrates the best wear resistance, with an average friction coefficient of 0.16.